2022
DOI: 10.3329/bjms.v21i1.56352
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bacterial contamination of blood components in a tertiary care centre

Abstract: not available Bangladesh Journal of Medical Science Vol. 21(1) 2022 Page : 213-215

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…18 Sehgal et al, reported a positive bacterial culture in 5.38% of platelet concentrates in PRP, while another research conducted in a blood bank in Ethiopia showed a very high bacterial contamination rate in 4 platelet bags out of a total of 12 bags tested. 19,20 Our results were similar to those reported in a Moroccan blood bank which analyzed platelet concentrates over seven years and reported culture positivity of 0.44%. 21 Bacterial contamination screening was introduced in Australian blood banks in 2008, and researchers have demonstrated a decline in the initial machine culture positivity rate in platelet concentrates of 0.6% since 2013.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…18 Sehgal et al, reported a positive bacterial culture in 5.38% of platelet concentrates in PRP, while another research conducted in a blood bank in Ethiopia showed a very high bacterial contamination rate in 4 platelet bags out of a total of 12 bags tested. 19,20 Our results were similar to those reported in a Moroccan blood bank which analyzed platelet concentrates over seven years and reported culture positivity of 0.44%. 21 Bacterial contamination screening was introduced in Australian blood banks in 2008, and researchers have demonstrated a decline in the initial machine culture positivity rate in platelet concentrates of 0.6% since 2013.…”
Section: Discussionsupporting
confidence: 89%
“…Sehgal et al, observed closely similar results where all RCCs were found sterile. 19 Our findings highlighted our staff's routine adherence to stringent blood donor arm disinfection technique and meticu-lous donor selection criteria, which mitigated the risk of bacterial sepsis.…”
Section: Discussionmentioning
confidence: 67%
“…[15][16][17][18][19][20][21][22] As for the genetic convergence between the two isolates (13 and 18), 80% were that the isolation (13), which is due to the phylogenetic group (A) and did not give a result for the serotype, this may be due to the presence of new patterns that have not been studied or because the methods of serotyping O-do not always indicate the exact pathogenicity of E. coli strains, and resistance to 5 antibiotics (Nakamura et al, 2021).Isolation (18), which is belong to the phylogenetic group (F), which owns the chuA gene and it included the serotype (O25:K11) and the percentage of genetic convergence between isolates (9,14,31) and isolates (13,18) by 88% and isolated from Al-Alawi Teaching Hospital. The fifth type, which includes each of the previously mentioned isolates (9,14,31,13,18) and isolates (2,7,20,5,26), includes the two isolates (2,7), the isolation (2) belongs to the phylogenetic group (F), which has chuA gene and belongs to the serotype (O142:K86).Isolation (7) belongs to the phylogenetic group (E), which has genes (TrpBA, arpA, ChuA), did not give a serotype, and the genetic convergence rate is 80%, both of which are transmitted through contaminated food, animals are the main reservoirs of many foodborne pathogens (Moxleyet al, 2020).The isolation (20) belongs to the phylogenetic group F, which has a gene (chuA), did not give a serotype, and resistance to 5 antibiotics, and the percentage of convergence is 88% between it and isolates (2,7) and the convergence rate between the two isolates (5,21) is 90%, as the isolation (5) belongs to the phylogenetic group (E), which included the serotype (O25:K11) and has the genes (TrpBA, arpA, ChuA, TspE4c2, yjaA), while the isolation (21) belongs to the phylogenetic group (D), which has genes (TrpBA, arpA, TspE4c2, ChuA) included the s...…”
Section: Resultsmentioning
confidence: 99%
“…E.coli belong to Enterobacteriacea family, which is one of the pathological bacteria normally inhabitant in the human gastrointestinal tract and its possession of many factors of virulence, and its resistance to antibiotics has become an important pathogen 1 , as it has the potential to opportunistically infect the human body whenever the necessary opportunity is available, causing several diseases (1)(2)(3) .The factors causing diarrhea in infants and young children who are under the age of five are due to bacterial causes and viral, parasitic and fungal pathogens, most of which are transmitted through water contaminated with feces, the bacterial causes are: Enter pathogenic Escherichia coli, Shigella species, Salmonella spp., Vibrio spp., Clostridia spp. 4,5 The first strains of E.coli that colonized in the intestines of the newborn may have come from the mother's feces during childbirth or may have been through lactation. 5 Although the number of studies is small, Diarrheagenic E.coli (DEC) is the most pathogenic isolate, especially in association with the consumption of contaminated food and water, in low-income countries it is responsible for more than 35% of hospitalizations from these children under the age of five, Studies show that more than 3 million individuals will lose their lives by 2050 through MDR E. coli, which are spreading worldwide, MDR E.coli is now recognized as one of the greatest public health challenges worldwide (Magiorakos et al,2020; Al-Kalifawi and Al-Azzawi has increased mainly due to the possession of βlactamases enzymes and imipenem resistance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation